No offence. Series 3 [videorecording (DVD)] - Scanlan, Joanna; Cassidy, Elaine, 1979-; Roach, Alexandra, 1987-; Mellor, Will, 1976- (Acorn Media, 2019)
DI Vivienne Deering and her team provide security at a contentious election debate, but tragedy strikes when a shooter attempts to assassinate one of the candidates. Deering and her right-hand woman, DC Dinah Kowalska, vow to apprehend the culprit, despite warnings from their superiors that the investigation could jeopardize an undercover officer who has infiltrated an extreme right-wing group.